Collaborative groups: a reflective look for the professional development of mathematics teachers (Research, Society and Development, 2018)
The present work aims to present the conceptual characteristics about collaborative groups and to identify their importance in the professional development process of teachers who teach Mathematics. For this, we adopt a methodology of bibliographic research in which we bring authors who discuss this theme. Our theoretical framework is supported by authors who discuss the importance of collaborative groups in the teaching of Mathematics. The results show that the collaborative groups contribute to the professional development of teachers by promoting, through reflexivity, spaces of collective discussions about the practice of teachers in the classroom.